PRELIMENARY REPORT ON TETRAMERES INFECTION IN A CHICKEN - A. Abdul-Aziz , T.; A. Al-Attar‎, M. (The Iraqi Journal of Veterinary Medicine, 1986)
Tetrameres was diagnosed in a free-range-reared chicken. Macroscopically, there were dark spots on the subserosal surface of the proventricular wall; small dark red nodules were present on the cut surface of the proventricular wall. Histologically, each of the nodules was a Tetrameres female in a greatly distended lumen of a gastric gland lobule.